Self-care and lifestyle interventions of complementary and integrative medicine during the COVID-19 pandemic—A cross-sectional study - Jeitler, Michael; Erehman, Avital; Koppold, Daniela A.; Ortiz, Miriam; Jerzynski, Lea; Stöckigt, Barbara; Rotter, Gabriele; Blakeslee, Sarah; Brinkhaus, Benno; Michalsen, Andreas; Seifert, Georg; Cramer, Holger; et al. (Frontiers in Medicine, 2023)
Background Complementary and Integrative Medicine (CIM), including self-care healthy life-style promotion strategies, is widely used in Germany. Aim of this study was to assess the use of self-care and lifestyle interventions as well as mental/emotional state experienced during the COVID-19 pandemic. Methods An exploratory cross-sectional online study was conducted with adults in Germany through an online survey. Custom-developed questions in respiratory disease-status (including COVID-19), CIM-based self-care/lifestyle interventions and dietary patterns, and mental/emotional state as well as parameters for wellbeing (World Health Organization Well-Being Index, WHO-5) and self-efficacy (General Self-Efficacy Short Scale, GSE-3) were assessed. Data was analyzed using frequency and parametric measures. Results The online survey was performed from January to March 2021 and included 1,138 participants (81.5% female; mean age: 49.2 ± 13.7 years; 54.9% holding a university degree) living in Germany, of which 62 had had a positive SARS-CoV-2 test, 4 an influenza infection and 375 participants other respiratory infections. The following individual health promotion strategies were reported: spending time in nature (90%; n = 1,024), physical activity (69.3%; n = 789), naturopathic remedies (63.1%; n = 718), plant-based diet (56.3%; n = 640), and Mind-Body interventions (54.7%; n = 623). No differences in strategies between individuals with respiratory diseases or the sample overall were found. Well-being had a mean value of 15.2 ± 5 (WHO-5) and self-efficacy 4.1 ± 0.6 (GSE-3). Nearly 8% reported a low mental/emotional state regarding the COVID-19 pandemic. Conclusion Self-care and lifestyle interventions during the COVID-19 pandemic were reported by participants who were predominantly female, middle-aged, and well-educated. Most participants showed an overall balanced mental/emotional state. Further studies should include a representative control group from the general population. Clinical trial registration clinicaltrials.gov, identifier NCT04653727.